An Estimation of Greenhouse Gas Emission from Livestock in Nepal - Ghimire, Urusha; Sharma, Bhubaneshwar; Pandit, Arjun; Upreti, Chet Raj (Nepalese Journal of Agricultural Sciences, 2026)
This study estimates and projects livestock-related greenhouse gas (GHG) emissions in Nepal between 2002 and 2022, providing crucial insights for climate change mitigation strategies. The latest secondary data on livestock population was collected from the Ministry of Agriculture and Livestock Development (MoALD) Nepal. The IPCC tier 1 methods were used to estimate emissions and forecast future trends. Studies reveal that Nepal livestock-related GHG emissions reached 28,603Gg CO2 e /year in 2022,with buffalo accounting for 39 % of the total emissions followed by cattle and goats. In 2022, the primary sources of emissions were direct nitrous oxide (48.2%), enteric methane (44.7%), manure methane (4.5%), and indirect nitrous oxide (0.6%). Future projections indicate a potential increase in total GHG emissions by 3.06 % and 3.56% up to 2050, suggesting a growing environmental impact if current practices continue. The provincial (regional) analysis identified Koshi province as the highest emitter in 2022. This research underscores the need for effective management strategies to mitigate emissions from the livestock sector in Nepal. Further, it recommends transitioning to the IPCC Tier 2 approach when sufficient national-level data becomes available to enhance the accuracy of future inventories